Analisis Penerimaan Aplikasi Indriver dengan Menggunakan Pendekatan Modified Technology Acceptance Model - Hendrawan, Bonny; Hartanto, Tomi; Wulansari, Sendy (Syntax Idea, 2021)
This research is based on testing whether the price that can not be done, the card, the numbered reading power and usefulness are bernyimat and intention for the user of the system in the applicationdriver. The Indriver Application System Acceptance analysis uses the exemplary Technology Acceptance click model. The data is from user applications from 100 indrivers in South Jakarta with a cavalier online questionnaire. The data analysis was conducted using the Element-Partial Least Square (SEM-PLS) Compliant Model using SmartPLS3. The results of the 2020 price price and positive effects and energy on the use of indriver namedn. Easy pricing has a positive effect but not as low as indriver price. Plant-based power may have a positive and energizing effect on the user on the indriver. Its chewing uses are positive effects and energy on indriver users. The service room has a positive effect and speaks to its obvious uses. Room service services have a positive effect but not good on users in the year indriver. User promo users have a positive effect and very intent intention to driver on on. Located from the results of the study and above, it can be concluded that the price is positive and wide spread perception perception statistically.